Perubahan nilai tukar mata uang terhadap impor dan dampaknya terhadap pertumbuhan ekonomi indonesia - Aini, Qurrotul (Maliki Interdisciplinary Journal, 2024)
Changes in currency exchange rates have a significant impact on Indonesian imports. This article analyzes the various effects of exchange rate fluctuations on prices of imported goods, inflation, trade balance, industrial sectors, and consumption and investment. A weakening of the rupiah exchange rate tends to increase import costs, which in turn can trigger inflation and affect the trade balance. Industrial sectors that depend on imported raw materials will face increasing production costs, reducing the competitiveness of domestic products. Exchange rate instability also creates economic uncertainty, affecting consumption and investment decisions. The government often responds with economic policies to maintain exchange rate stability and reduce its negative impacts. Exchange rate stability is very important to maintain a healthy and sustainable Indonesian economy.